The Swedish two county trial of mammographic screening for breast cancer: recent results and calculation of benefit. - Tabar, L (1989)
The Swedish two county trial of breast cancer screening is now in its tenth year. This paper presents detailed results on mortality from breast cancer and from all other causes, and on the population denominators at risk for each of the first 8 years of follow up, for each county separately. These data represent a two year update on the last major report. Results show an increasingly significant deficit in deaths from breast cancer among the 77,092 women invited to screening relative to the 56,000 not invited (RR = 0.68, p = 0.002), with no significant difference between the effects of screening in the two counties (p = 0.5). These results remain the same when adjusted for age. Analysis of all cause deaths shows no significant effect of screening (p = 0.5), nor was there any significant effect of screening on deaths from all causes other than breast cancer (p = 0.9). The rates of deaths from intercurrent illness in breast cancer cases were almost identical in the group invited to screening and the group not invited (p = 0.7). This result remained the same when adjusted for age. We calculate that in the age group 50-69 at entry, one breast cancer death was prevented per 4000 woman/years, per 1460 mammographic examinations, per 13.5 biopsies, and per 7.4 breast cancers detected.